The correlation between critical thinking skills of junior high school students with decision-making on the use of plastic bags - Sasha Elitzsar Latfia; Mimin Nurjhani Kusumastuti; Yanti Hamdiyati (Assimilation: Indonesian Journal of Biology Education, 2022)
This study was based on the urgency of critical thinking skills and decision making as part of Higher Order Thinking Skills which students need to master, in addition to the abundance of issues about the dangers resulting from the use of plastic bags related to the environmental pollution topic. The aims of this study were to describe the critical thinking skills and decision making; and to identify the correlation of critical thinking skills with decision making. The method of this study was correlational which involved 30 students of 7th grade of junior high school in SMPN 1 Lembang. The research data were collected by using critical thinking skills test and decision making skills test in the form of an essay. The correlation of both skills were analyzed by using Spearman’s rho Correlation Test using SPSS 16.0, as for interview as the complement. The findings of this study showed that the mean values of both skills are categorized as good. In critical thinking, question at issue, information, and assumptions indicators are categorized as “moderate”; indicator of concept, interpretation and inference, also the implication and consequences are categorized as “good”; while indicator of purpose and point of view is categorized as “excellent”. In decision making, defining problems and evaluation indicators are categorized as “good”, while indicators of generating alternatives, checking risks and consequences, and selecting alternatives are categorized as “excellent”. Critical thinking skills and decision making of students on the use of plastic bags were found to have a significant correlation, positive, and moderate correlation level with 0.458 correlation coefficient. Therefore, it can be concluded that critical thinking skills have a positive correlation with student’s decision making skills on the use of plastic bags.